2023
DOI: 10.3390/v15112189
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Dependent Association of Torque Teno Virus Load with the Level of SARS-CoV-2 S1 IgG Antibodies Following COVID-19 Vaccination in Kidney Transplant Recipients

Céline Imhof,
Lianne Messchendorp,
Debbie van Baarle
et al.

Abstract: Kidney transplant recipients (KTR) show an impaired humoral immune response to COVID-19 vaccination due to their immunocompromised status. Torque teno virus (TTV) is a possible marker of immune function. This marker may be helpful in predicting the immune response after COVID-19 vaccination in order to decide which vaccination strategy should be applied. We therefore investigated whether TTV load is associated with the humoral response after COVID-19 vaccination. Of the KTR who participated in two prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Upon further analysis, the authors indicated that this correlation was statistically significant solely among patients within a 24-month post-transplantation period. However, in individuals with a longer interval since NTx, this correlation was not observed [ 35 ].…”
Section: Role In the Prediction Of The Response To Vaccinationmentioning
confidence: 99%
“…Upon further analysis, the authors indicated that this correlation was statistically significant solely among patients within a 24-month post-transplantation period. However, in individuals with a longer interval since NTx, this correlation was not observed [ 35 ].…”
Section: Role In the Prediction Of The Response To Vaccinationmentioning
confidence: 99%